The effects of Lactobacillus fermentation on the quality changes and flavor characteristics of Aronia melanocarpa juice using physicochemical analysis and electronic nose techniques - Yitong Wu; Ruihan Chen; Minjun Liu; Yingyan Fang; Jinchong Wu; Junyi Chen; Xiaoping Yang; Ziying Fang; Xiang Fang; Sashuang Dong (Food Innovation and Advances)
Aronia melanocarpa is a fruit rich in antioxidant compounds with notable health benefits; however, its astringency limits its widespread consumption. This study examined the effects of fermentation with Lactiplantibacillus plantarum 1243 and Lacticaseibacillus paracasei 139 on the microbiological dynamics, quality indicators, and flavor profile of Aronia melanocarpa juice. The results showed that, compared to the unfermented juice, the microbial count reached 7.03 lg CFU/mL at 24 h of fermentation, followed by a decline to 3.90 lg CFU/mL at 96 h. Soluble sugars experienced an initial decline, subsequently increased, and then decreased again. Acidity firstly reduced and then increased, while pH increased initially and then decreased. Total phenolic and flavonoid contents remained relatively stable at 24 h before showing a significant reduction. The DPPH radical scavenging activity significantly increased during fermentation, reaching a peak of 71.7% at 48 h. Overall improvement was observed in color and sensory acceptance of the juice. Flavor analysis demonstrated an increase in aromatic organic compounds, aliphatic aromatics, and methyl compounds, contributing to aroma enhancement in Aronia melanocarpa juice. These findings establish a basis for the use of lactic acid bacteria fermentation to enhance the quality, flavor, and functionality of Aronia melanocarpa juice, supporting the development of functional beverages.